Predisposing factors for neonatal jaundice in patients discharged from neonatal ICU, in los Ángeles children’s Hospital in Pasto - Galíndez-González, Angie Lizeth; Carrera-Benavides, Sara Raquel; Díaz-Jiménez, Angely Alejandra; Martínez-Burbano, Mavir Bibiana (Universidad y Salud, 2017)
Introduction: Neonatal jaundice is one of the most common conditions in newborns; however, improper treatment can be harmful to the patient, despite being benign. Objective: To determine the predisposing factors of neonatal jaundice in patients discharged from the neonatal ICU of Los Angeles children’s Hospital in the city of Pasto (Nariño) between January 2007and August 2011. Materials and methods: An observational, descriptive, retrospective and quantitative study was conducted. 608 clinical histories of discharged infants diagnosed with neonatal jaundice were studied. The variables studied were analyzed with the complement of Excel, XLSTAT-Pro 7.5.2. Results: The main predisposing factors found in the population were exclusive breastfeeding and male gender in 87%, and 57.40% respectively; besides, 90.79% were newborns at term, 92.93% had adequate weight for their gestational age and 54.93% presented neonatal jaundice between 2 and 7 days of extrauterine life. Conclusions: Neonatal jaundice is associated with both modifiable and non-modifiable maternal and neonatal factors that can be addressed with appropriate strategies to reduce the burden of disease.